Diagnostic Accuracy Of Barium Swallow For Dysphagia, Keeping Rigid Esophagoscopy As The Gold Standard - Ansa Umara Akram; Sadia Chaudhry; Sundas Masood; Amna Kausar; Seema Naveed; Areesha Manzoor (Journal of Rawalpindi Medical College)
Objective: To determine the diagnostic accuracy of Barium Swallow in detection of patients presenting with dysphagia.